The Thought of Smart villages based on Internet of Things and WSN - Kansari, Mukesh; Sharma, Anurag (International Journal of Computer Sciences and Engineering, 2025)
the plan of Internet of Things (IoT) and Wireless Sensor Network is the expectations vision of technology. The basis following its working be the merger of network, web server, mobile and data or Information and connections tools. It enables a variety of devices or strategy in a scheme to converse and act together through every new to carry out their job in a pleasant-sounding method [27]. and the Wireless sensor networks (WSNs) are work of fiction major wireless networks with the meaning and consist of distributed, low-power, small-size policy using sensors to helpfully bring together information from beginning to end infrastructure less ad-hoc wireless network[16] The rising population of the world makes it essential to smooth the progress of the cities and villages to role in a smart way. Hence, the thought or design of Smart cities came addicted to organism. These cities utilize the information or data from sensors and using a wireless sensor network technology, other remote devices and evaluate the data to take suitable events. This paper extends the plan of Smart cities to Smart villages and using an IoT and WSN. It focuses resting on the key areas of concern in the village viewpoint and evaluates the applications of IoT and WSN in those areas. It provides a wide-ranging vision in the midst of high opinion to development in the quality or excellence of life in villages or cities.